Changes in Energy Demand of Dance Activity and Cardiorespiratory Fitness During 1 Year of Vocational Contemporary Dance Training. Issue 3 (March 2018) - Beck, Sarah; Wyon, Matthew A.; Redding, Emma
Abstract : Abstract: Beck, S, Wyon, MA, and Redding, E. Changes in energy demand of dance activity and cardiorespiratory fitness during 1 year of vocational contemporary dance training. J Strength Cond Res 32(3): 841–848, 2018—Previous literature has demonstrated that the intensity of dance class as well as its discontinuous nature is not sufficient to elicit an aerobic training response and that the aerobic capacity of dancers is relatively low. These findings have raised questions on the suitability of training, through class and rehearsal, as adequate preparation for the physical demands of performance and a sustained, successful career in dance. The aim of this study was to describe changes in aerobic fitness and energy cost of dance movement occurring throughout 1 year of training. Subjects were 13 female dance students; 7 first-year undergraduate (UG) students, and 6 postgraduate (PG) students. At 3 time points (TP1, TP2, and TP3) during 1 academic year, each subject completed a treadmill test to determine V[Combining Dot Above]O2 peak (ml·kg −1 ·min −1 ) and lactate threshold (LT) (ml·kg −1 ·min −1 and %V[Combining Dot Above]O2 peak) and a standardized 4-minute dance sequence, where the mean demand was expressed as V[Combining Dot Above]O2 (ml·kg −1 ·min −1 ), heart rate (b·min −1 ), %V[Combining Dot Above]O2 peak, and %LT. Both groups displayed an overall decrease in mean V[Combining Dot Above]O2 peak throughout the year, despite a peak in fitness at TP2 in the PG students. No significant changes in LT were noted over time for either group. A significant reduction in the relative intensity of the dance sequence, particularly in relation to mean VO2 (ml·kg −1 ·min −1 ) and %LT data, was observed over time in both groups, although the degree of change was less in the UG group than the PG group. Apparent adaptations during a rehearsal period in the PG group are presented in contrast to previous research findings. Recommendations for future research include further investigation into the energy demand of rehearsal and cardiorespiratory adaptation during rehearsal periods as well as further reporting of measures related to LT and movement economy.